Mutagenic effect of ion beam irradiation on survival and seedling growth characters of malaysian rice (Oryza sativa l.) variety mr84 - Hasan, Nor’aishah; Rafii, Mohd Y.; Abdul Rahim, Harun; Ahmad, Faiz (Agri Bio Research Publishers, 2020)
Ion beam irradiation has emerged as an excellent tool for mutation breeding to produce new promising mutant variety. Ion beam has been found to show high relative biological effectiveness (RBE) of growth inhibition. The effects of ion beam radiation were investigated by studying seed germination, seedling growth and survival of rice variety MR84. Mature and healthy seeds of variety MR84 were irradiated by 320 MeV carbon-ion beam irradiation : at Japan Atomic Energy Research Institute (JAERI, Japan) within a dose range of 0, 10, 20, 40, 60, 80 and 100 Gray (Gy). The 50% lethal dose (LD50) for ion beam irradiation under in vitro condition was fixed at 52.78 Gy based on probit analysis. As the dosage of applied ion beam irradiation increased, the root length and vigour index in M1 generation decreased as compared to the control. The maximum seedling growth was observed in 20 Gy with 17.33 cm of shoot length, 18.53 cm of root length and 35.87 cm of plant height, while the minimum seedling growth was monitored in 100 Gy. Based on the vigour index trait, it can be suggested that doses between 10.46 to 27.92 Gy were found to be a suitable starting point for mutagenesis without drastically impairing growth and survival.